Ultimate Load Capacity of Composite Concrete-SteelDeck One Way Slab - M. Salman, Mohammed; A. Waryosh, Waleed; Habeeb Hashem, Uday (Journal of Engineering and Sustainable Development, 2006)
Ultimate capacity of composite concrete-steel deck (a composite slab) is the topic of this study. A composite slab consists of two or more structural components of different materials. The main aim of using a composite slab is to make full use of the beneficial properties of different materials. The upper and lower components in a composite slab are usually connected together by shear connectors. The present study is concerned with the ultimate capacity of composite concrete-steel deck-one way slabs (composite slabs), the ultimate capacity of composite slabs with longitudinal bars and ultimate capacity of composite slabs with shear reinforcement. The study also includes the effect of using different spans of steel decks.The tested slabs are loaded to failure by means of two-point load tests. It is found that a composite slab with longitudinal bars (RLB) gives high Ultimate load capacity. The mean ratios of ultimate load capacity for the composite slabs with longitudinal bars (RLB) to reference slabs (RS) are (1.78) and (1.98) of slabs which have length equal to (1600mm) and (1300mm), respectively.